FAKTOR-FAKTOR YANG BERPERAN TERHADAP PENINGKATAN SIKAP KESELAMATAN DAN KESEHATAN KERJA (K3) PARA PELAKU JASA KONSTRUKSI DI SEMARANG - Endroyo, Bambang (Semarang State University, 2010)
Abstract:ÃÂ ImplementationÃÂ of Occupational HealthÃÂ and SafetyÃÂ (K3),ÃÂ especiallyÃÂ inÃÂ theÃÂ construction sector was still bad. K3ÃÂ inÃÂ IndonesiaÃÂ is haveÃÂ theÃÂ lowestÃÂ rankÃÂ in Asean. Various efforts have been made by governmentÃÂ to reduce occupational accidentsÃÂ to a minimum as possible. Accidents often occur were mostly caused by humanÃÂ factors,ÃÂ ÃÂ about 85%. Construction SafetyÃÂ ImplementationÃÂ in the field depends on the attitude and the behavioral of the participant of construction services. The attitude of K3 depends on many factors, among others - which will be studied through this research - are: education, experience, certification, and corporate commitment. FromÃÂ these variousÃÂ factors, educationalÃÂ factorsÃÂ correlatedÃÂ 0.30ÃÂ (significance:ÃÂ 0.048)ÃÂ contributeÃÂ toÃÂ attitudeÃÂ ofÃÂ K3ÃÂ ,ÃÂ andÃÂ was anotherÃÂ factorÃÂ correlationsÃÂ wereÃÂ notÃÂ significant.ÃÂ AllÃÂ theseÃÂ factorsÃÂ have ÃÂ onlyÃÂ toÃÂ giveÃÂ efectif contribution aboutÃÂ to 0.213ÃÂ (21.3%) ofÃÂ the attitudeÃÂ factor K3.ÃÂ It meansÃÂ that about ofÃÂ ÃÂ 78.7% hich can not be explained and is a problem to be studied again. Key words: attitude of K3, construction, participant of construction services ÃÂ Abstrak:ÃÂ ÃÂ ÃÂ PelaksanaanÃÂ KeselamatanÃÂ danÃÂ KesehatanÃÂ KerjaÃÂ (K3)ÃÂ terutamaÃÂ diÃÂ sektorÃÂ konstruksi masih memprihatinkan.ÃÂ K3ÃÂ diÃÂ Indonesia masih mendudukiÃÂ urutanÃÂ terbawahÃÂ diÃÂ Asean.ÃÂ Berbagai upayaÃÂ telahÃÂ dilakukanÃÂ olehÃÂ pemerintahÃÂ untukÃÂ menekanÃÂ kecelakaanÃÂ kerjaÃÂ menjadiÃÂ seÃÂ minimal mungkin. KecelakaanÃÂ yangÃÂ seringÃÂ terjadi banyak diakibatkan olehÃÂ faktor manusiaÃÂ (humanÃÂ factor) yaituÃÂ sebesarÃÂ 85%.ÃÂ PelaksanaanÃÂ K3ÃÂ KonstruksiÃÂ diÃÂ lapanganÃÂ sangatÃÂ tergantungÃÂ dariÃÂ sikapÃÂ dan perilakuÃÂ para pelakuÃÂ jasaÃÂ konstruksi. Sikap K3ÃÂ sangatÃÂ tergantungÃÂ dariÃÂ banyakÃÂ faktor, antaraÃÂ lain yangÃÂ akanÃÂ diungkapÃÂ melaluiÃÂ penelitianÃÂ iniÃÂ adalah:ÃÂ pendidikan,ÃÂ pengalaman,ÃÂ sertifikasi,ÃÂ dan komitmenÃÂ perusahaan. DariÃÂ berbagaiÃÂ faktorÃÂ tersebut,ÃÂ faktorÃÂ pendidikan mempunyaiÃÂ korelasiÃÂ ,30 (signifikansi: 0,048)ÃÂ terhadap sikap K3, sedangÃÂ faktorÃÂ lainnya korelasinyaÃÂ tidak signifikan. Semua faktorÃÂ tersebut hanya memberi memiliki sumbangan efektif sebesar 0,213 (21,3%)ÃÂ terhadapÃÂ faktor sikapÃÂ K3.ÃÂ ÃÂ ÃÂ HalÃÂ ituÃÂ menunjukkanÃÂ bahwaÃÂ masihÃÂ adaÃÂ ÃÂ ÃÂ 78,7ÃÂ %ÃÂ yangÃÂ belumÃÂ dapatÃÂ dijelaskanÃÂ dan merupakan masalah yang masih harus diupayakan jawabnya. Kata kunci: sikap K3, konstruksi, pelaku jasa konstruksi